IMPLEMENTASI PROGRAM PESANTREN RAMAH ANAK SEBAGAI UPAYA PENCEGAHAN PERILAKU BULLYING DI KALANGAN SANTRI (STUDI KASUS DI PONDOK PESANTREN AL BASYARIYAH BANDUNG) - Sanjaya, Dinar; Dianawati Wasliman, Eva (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Bullying in educational settings remains a serious issue with significant academic, social, and psychological consequences for students, including those in Islamic boarding schools (pesantren). The residential nature of pesantren, characterized by 24-hour supervision, intensive social interaction, and hierarchical relationships, presents both opportunities for character formation and risks of unmonitored bullying practices. In response to this challenge, the Child-Friendly Pesantren Program (Program Pesantren Ramah Anak/PRA) was developed to integrate child protection principles into pesantren governance and daily practices. This study aims to analyze the implementation of the Child-Friendly Pesantren Program as an effort to prevent bullying among students at Pondok Pesantren Al-Basyariyah Bandung. Employing a qualitative case study approach, data were collected through in-depth interviews, participant observation, and document analysis. Data analysis was conducted inductively using the Deming PDCA (Plan–Do–Check–Act) quality management framework. The findings indicate that the PRA program is implemented through the reinforcement of religious-humanistic values, role modeling by caregivers, the institutionalization of non-violent disciplinary practices, and the establishment of a Student Guidance and Counseling Unit (BK-Santri) serving both preventive and remedial functions. These initiatives have contributed to increased student awareness of empathy, improved access to safe reporting mechanisms, and a reduction in interpersonal conflicts and bullying incidents. However, challenges remain, particularly in the areas of systematic documentation, data-based evaluation, and dependence on key institutional actors. Overall, the study demonstrates that the Child-Friendly Pesantren Program has significant potential to create a safe, inclusive, and sustainable educational environment when supported by a continuous quality improvement approach based on the PDCA cycle.